Glacier expansion on Baffin Island during early Holocene cold reversals. (1st August 2020) - Crump, Sarah E.; Young, Nicolás E.; Miller, Gifford H.; Pendleton, Simon L.; Tulenko, Joseph P.; Anderson, Robert S.; Briner, Jason P.
Abstract: The North Atlantic was a key locus for circulation-driven abrupt climate change in the past and could play a similar role in the future. Abrupt cold reversals, including the 8.2 ka event, punctuated the otherwise warm early Holocene in the North Atlantic region and serve as useful paleo examples of rapid climate change. In this work, we assess the cryospheric response to early Holocene climate history on Baffin Island, Arctic Canada, using cosmogenic radionuclide dating of moraines. We present 39 new 10 Be ages from four sets of multi-crested early Holocene moraines deposited by cirque glaciers and ice cap outlet glaciers, as well as erratic boulders along adjacent fiords to constrain the timing of regional deglaciation. The age of one moraine is additionally constrained by in situ 14 C measurements, which confirm 10 Be inheritance in some samples. All four moraines were deposited between ∼9.2 and 8.0 ka, and their average ages coincide with abrupt coolings at 9.3 and 8.2 ka that are recorded in Greenland ice cores. Freshwater delivery to the North Atlantic that reduced the flux of warm Atlantic water into Baffin Bay may explain brief intervals of glacier advance, although moraine formation cannot be definitively tied to centennial-scale cold reversals. We thus explore other possible contributing factors, including ice dynamics related to retreat of Laurentide Ice Sheet outlet glaciers. Using a numerical glacier model, we show that the debuttressing effect of trunk valley deglaciation may have contributed to these moraine-building events. These new age constraints and process insights highlight the complex behavior of the cryosphere during regional deglaciation and suggest that multiple abrupt cold reversals—as well as deglacial ice dynamics—likely played a role in early Holocene moraine formation on Baffin Island. Highlights: 39 new 10 Be dates constrain the age of early Holocene moraines and fiord deglaciation. In situ 14 C confirms inherited 10 Be in some samples and clarifies moraine exposure age. Moraine average ages overlap with known abrupt climate events at 9.3 and 8.2 ka. A numerical model shows deglacial ice dynamics may also affect moraine formation.